2021
DOI: 10.29289/2594539420200085
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of women with breast cancer in a public hospital in the Federal District of Brazil

Abstract: Introduction: In Brazil, for the 2020–2022 triennium, the estimated incidence of breast cancer in women was 66,280/year. It is the most incident type of cancer in all Brazilian regions. Several risk factors are associated with the probable etiology of breast cancer, though the complexity of the disease makes it difficult to define its main cause. Objective: To investigate the prevalence of factors associated with breast cancer in an outpatient population at a public hospital in the Federal District, and to ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
3
0
0
Order By: Relevance
“…However, the mechanisms by which smoking influences BC risk are not fully understood. Our studies have found only 30.7% of patients smoke and it was similar to other research [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the mechanisms by which smoking influences BC risk are not fully understood. Our studies have found only 30.7% of patients smoke and it was similar to other research [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, alcohol may interfere with the body's ability to metabolize and eliminate carcinogens, further contributing to the development of breast cancer [10]. In our study, 41.3% of women with BC reported being an alcoholic or former alcoholic, corroborating other studies in the Brazilian Amazon region [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation